Development of Augmented Reality (AR) Based Learning Media to Improve Educational Outcomes for Elementary School Students - Nurachmadani, Nadila; Sahudra, Tengku Muhammad; Mulyahati, Bunga (ALACRITY : Journal of Education, 2025)
This research focuses on creating a learning media product that utilizes Augmented Reality (AR) for teaching IPAS, particularly aimed at fifth-grade students in Social Studies. The study was conducted to evaluate the validation from experts in media, subject matter, and student testing, as well as to assess the practicality and effectiveness of student learning outcomes after engaging with the AR-based learning media. Utilizing a Research and Development (R&D) methodology, this study follows the ADDIE model, which includes five phases: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques used include observation, interviews, documentation, and validation questionnaires for experts, as well as response questionnaires for teachers and students.The validation results from media experts showed a percentage of 97.14% with a "highly feasible" criterion, material experts obtained a percentage of 92.5% with a "highly feasible" criterion, and test experts achieved 100% with a "highly feasible" criterion. The practicality results from teacher and student response questionnaires indicated that teachers gave a response percentage of 100% with a "highly practical" criterion, while students' responses reached 93.34% with a "highly practical" criterion. Furthermore, student learning outcomes were measured using Normality Test (N-Gain), resulting in a score of 73.58% with an "effective" criterion. Based on the assessment results, it can be concluded that the AR-based learning media for IPAS learning in fifth grade is highly feasible for use in education. Future researchers are advised to conduct field trials, measure the effectiveness of teaching materials, and further develop AR-based learning media for various subjects in elementary schools.